2021
DOI: 10.1038/s41416-021-01382-1
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated help-seeking for cancer symptoms before and after the coronavirus pandemic: results from the Onco-barometer population survey in Spain

Abstract: Background The patient interval—the time patients wait before consulting their physician after noticing cancer symptoms—contributes to diagnostic delays. We compared anticipated help-seeking times for cancer symptoms and perceived barriers to help-seeking before and after the coronavirus pandemic. Methods Two waves (pre-Coronavirus: February 2020, N = 3269; and post-Coronavirus: August 2020, N = 1500) of the Spanish Onco-barometer population survey were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Similarly to previous research, key help-seeking barriers in the current study included worry about wasting healthcare professionals’ time, overstretching limited healthcare resources and accessing healthcare services (personal communication). 28 35 In a Spanish population sample, Petrova et al 36 also reported barriers to anticipated symptom help-seeking during the COVID-19 pandemic including worry about wasting the doctor’s time and worry about what the doctor might find. International prepandemic research on barriers to help-seeking has found that UK adults are more likely to report worry about ‘bothering the doctor’ compared with those in other high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to previous research, key help-seeking barriers in the current study included worry about wasting healthcare professionals’ time, overstretching limited healthcare resources and accessing healthcare services (personal communication). 28 35 In a Spanish population sample, Petrova et al 36 also reported barriers to anticipated symptom help-seeking during the COVID-19 pandemic including worry about wasting the doctor’s time and worry about what the doctor might find. International prepandemic research on barriers to help-seeking has found that UK adults are more likely to report worry about ‘bothering the doctor’ compared with those in other high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Many individuals have delayed consulting for cancer‐related symptoms due to access barriers, or fears of infection with coronavirus in a healthcare setting. 3 , 4 Healthcare staffing shortages may occur due to redeployment to the pandemic response, leave due to coronavirus infection, burnout or increased childcare responsibilities. Key cancer diagnostic tests, such as endoscopies, colonoscopies, mammographies, computerized tomography (CT) scans and magnetic resonance imaging (MRI) scans, have declined, 5 , 6 either due to fewer patient referrals or delays in accessing these services.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of 7543 adults in the UK found that approximately half of patients who reported experiencing cancer alarm signs and symptoms did not contact their general practitioner (GP) due to concerns about catching or transmitting COVID-19 [ 11 ]. Another survey of 3269 individuals in Spain found that participants reported significantly longer waiting times to help-seeking for cancer symptoms due to fears of overburdening the healthcare system during the pandemic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%